Pola Asuh Orang Tua Karir dalam Menanamkan Karakter Religius Pada Anak di Desa Cungkup Kecamatan Pucuk Kabupaten Lamongan - Rahmah, Eka Shilatur; Suradji, Muchamad; Ni’mah, Khoirotun (AJER: Advanced Journal of Education and Religion, 2025)
Parenting style can be defined as a pattern of interaction between parents and children that includes fulfilling physical needs, psychological needs and teaching socialization of norms in society. In this case, parents have their own ways or patterns in raising children. There are several types of parenting styles, including democratic, permissive, and authoritarian. By implementing an approach based on affection, providing role models, building valuable communication, and utilizing time together effectively, parents can still play a role as the main figures in instilling religious values in children. The objectives of this paper are: (1) to understand the parenting patterns of career parents in Cungkup Village, Pucuk District, Lamongan Regency (2) to understand and analyze how career parents instill religious character in children in Cungkup Village, Pucuk District, Lamongan Regency. In this study, using a qualitative descriptive method with a phenomenological approach, the data collection was done using interview, observation, and documentation methods. From the results of this study it can be seen that the parenting patterns applied in Cungkup Village, Pucuk District, Lamongan Regency, there are 2 types, namely democratic parenting patterns, and authoritarian parenting patterns. Meanwhile, in instilling religious character in the form of values that include social morals, discipline, and responsibility. In addition, there are several methods applied by career parents including instilling the value of monotheism, instilling morals and ethics, being a role model, and managing time with parents. The parenting style of career parents is not solely hampered by work commitments, but rather demonstrates flexibility and creativity in maintaining children’s character education so that it remains in line with Islamic values.